Comparison of deferasirox and deferoxamine effects on iron overload in patients with blood transfusion-dependent β-thalassemia - Wohab, Md Abdul; Hossain, Md Belayet; Choudhury, Nilufar Akhter Banu; Ara, Umme Nusrat (International Journal of Medical Research and Review, 2024)
Introduction: Beta-thalassemias is autosomal recessive hematological disorder prevalent in the Mediterranean area due to defects in synthesis of β chains of hemoglobin. The aim of present study was to compare the effects of deferasirox and deferoxamine on iron overload in patients with blood transfusion-dependent β-thalassemia major and intermedia. Patients And Methods: This study involved 100 patients with known cases of β-thalassemia major or intermedia that has been treated with blood transfusion and iron chelators from January 2020 to December 2023. Serum ferritin, serum iron, serum total iron binding capacity were assessed in deferoxamine and deferasirox-treated patients. Results: In deferoxamine-treated patients, serum ferritin levels were high (4600.56 + 119.2ng/dL) compared to deferasirox-treated patients (3000.261 ± 121.2 ng/dL; P< 0.0001), also there were significant differences in serum iron and total iron-binding capacity (P< 0.0001) in deferasirox-treated patients compared to deferoxamine-treated patients. Conclusion: This study indicated that deferasirox is more effective than deferoxamine regarding the iron overload in patients with blood transfusion-dependent β-thalassemia.